2016
DOI: 10.1371/journal.pone.0168290
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacterial Infections in a French Hospital: A 12-Year Retrospective Study

Abstract: BackgroundNontuberculous mycobacteria (NTM) are environmental organisms associated with a range of infections. Reports of NTM epidemiology are mainly focused on pulmonary infections and isolations, and extrapulmonary infections are less frequently described.MethodsWe conducted a retrospective study of NTM infections at the Bordeaux University Hospital, France, between January 2002 and December 2013. We used the microbiologic component of the American Thoracic Society/Infectious Diseases Society of America's pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 33 publications
5
20
0
1
Order By: Relevance
“…On the other hand, M . avium also showed a higher (66.7%) clinical relevance, which resembles similar findings from other part of the world [ 3 , 23 , 26 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, M . avium also showed a higher (66.7%) clinical relevance, which resembles similar findings from other part of the world [ 3 , 23 , 26 ].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, increased frequency of genetic predisposing conditions among the Saudi nationals mainly due to higher rate of consanguinity, increasing rate of different immunosuppressive therapies and various malignancies could be additional risks factors to increase the susceptibility to NTM infections [ 20 – 22 ]. Current data showed, individuals aged above 60 years were under particular risk of NTM infections, similar to studies reported with a higher isolation rate of NTM’s among elderly from Saudi Arabia and rest of the world [ 3 , 12 , 23 ]. Positive HIV cases were very much limited (2.6%) and comparably lower to other countries.…”
Section: Discussionsupporting
confidence: 86%
“…It should be stressed that all authors agreed that patients with NTM infection were older than those with tuberculosis and were usually 60+. Comparable NTM pattern to our current results was also observed in the retrospective study conducted in Bordeaux, France over 12years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) [18]. However, such stable trend among mycobacterial species over the years is not a typical phenomenon.…”
Section: Discussionsupporting
confidence: 86%
“…chelonae and M. xenopi dominate [17]. Few recent studies from South America have revealed that MAC is generally the most common there, and M. kansasii is also frequent [17][18][19][20][21]. Similarly, MAC is predominant in South Asia and in Queensland, Australia, whereas MAC with M. fortuitum and simiae in the Middle East [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…14 Ekspektativno stajalište motivirano je činjeni cama da je svega 20 -40% plućnih izolata NTM-a pove zano s bolešću, da rezultati testova osjetljivosti pojedinih NTM-a na antibiotike in vitro ne koreliraju s rezultatima in vivo pa se njihovom primjenom ne mogu predvidjeti klinički i bakteriološki odgovor na liječenje, 9,14,15,16 da ne postoji dovoljno kontroliranih studija koje bi se bavile procjenom rizika od progresivne plućne bolesti 17 što će ga bolesnici steći, kao i identifikacijom prediktora smrtnosti kod bolesnika 8 te da je stopa relapsa ili reinfekcije visoka, pogotovo u slučaju infekcije s M. avium. 18,19 Pritom treba posebno naglasiti da je riječ o sporoprogredirajućoj bole sti koja ostavlja dovoljno vremena za temeljitu dijagno stičku obradu svedenu na isključenje drugih bolesti što bi mogle davati slične simptome i radiološke nalaze, pogla vito tuberkulozu i karcinom pluća, kao i bakteriološku analizu dodatnih respiratornih uzoraka. 7 Upravo stoga od luka o započinjanju liječenja treba se temeljiti na objek tivnoj procjeni prednosti i rizika kojima može biti izložen bolesnik koji mora skupu i potencijalno toksičnu antibiot sku terapiju uzimati više od godinu dana.…”
Section: Ntm Strains Frequency Of Isolates and Episodes Of Isolationsunclassified